2:34 PM

3:27 PM
Hey @Adám, do you think I can golf this any further?

3:42 PM
@J.Sallé `⊣⊃⊢=⊣⊃∘⌽⊢`
@J.Sallé Actually, just `⊃=⊃∘⌽` !

@Adám Wow. How does this work, exactly?
No idea how `⊃` works with 2 arguments
Unless it just infers it's used dyadically because it's being passed 2 arguments?
Is it like `(⍺)⊃(⍵)=(⍺)⊃(⌽⍵)`?

@J.Sallé Yes, that is exactly it.

Nice, I got it then! Thanks as usual hahahah

4:09 PM
@J.Sallé Remember that a tacit function (like all functions) is either called monadically or dyadically. The type of calling also applies to every other function, beginning with the rightmost. (The ones in between are always called dyadically, and if there is one left on the far left, it is always called monadically.)

@Adám Ooooooooooh, I see! Makes a lot of sense, actually.

So for `a b c d e f` only `c` and `e` are always called dyadically. `b`, `d`, and `f` are called in whichever way the whole function is called. `a` is always called monadically.
@J.Sallé You're getting really good at this!

@Adám hahahah thanks man. APL is really fun and kinda forces you to think out of the box for some things.